Step II 1995 Q.1Watch

#21
(Original post by KeineHeldenMehr)
pff...still dont get it, S = 2(n+1)/4 magically appeared.
RHS = [-(2)(n+1)(-1)^n - (-1)^(n+1) + 1]/4

When n is even. (-1)^n = 1 and (-1)^(n+1) = -1.

Therefore RHS = (-2(n+1) + 1 + 1)/4

= (-2n-2+1+1)/4
=-n/2

Now, try it for when n is odd.
0
8 years ago
#22
(Original post by Clarity Incognito)
RHS = [-(2)(n+1)(-1)^n - (-1)^(n+1) + 1]/4

When n is even. (-1)^n = 1 and (-1)^(n+1) = -1.

Therefore RHS = (-2(n+1) + 1 + 1)/4

= (-2n-2+1+1)/4
=-n/2

Now, try it for when n is odd.
ahh gotcha, works!

thanks!
0
X

new posts
Latest
My Feed

Oops, nobody has postedin the last few hours.

Why not re-start the conversation?

see more

See more of what you like onThe Student Room

You can personalise what you see on TSR. Tell us a little about yourself to get started.

University open days

• University of the Arts London
MA Design: Ceramics, Furniture or Jewellery Open Day Postgraduate
Fri, 25 Jan '19
• Coventry University
Sat, 26 Jan '19
• Brunel University London
Sat, 26 Jan '19

Poll

Join the discussion

Are you chained to your phone?

Yes (109)
19.57%
Yes, but I'm trying to cut back (227)
40.75%
Nope, not that interesting (221)
39.68%